MULTIPLE SCHMORL’S NODES ON YOUNG ADULT WITH MYOFASCIAL PAIN SYNDROME: A CASE REPORT - I Gusti Agung Ayu Andra Yusari; Putu Gede Sudira; Ida Ayu Sri Wijayanti (MNJ (Malang Neurology Journal), 2023)
Background: Schmorl’s node (SN) is described as intraosseous disc herniations which penetrate into the spinal canal, which is caused by the weakening of the cartilaginous endplate and subchondral bone. SN is usually detected on imaging which appears small, focal, and rounded with varying degrees of adjacent reactive sclerosis. Case Report: We present a rare case of symptomatic SN in 25-year-old male patient with complaints of discomfort and muscle strain in the back. These complaints were exacerbated by physical exercise. Severe tenderness was found at several levels of the thoracic vertebrae during palpation, where the trigger points were found in the lower trapezius muscle. Computerized tomography (CT) scan of the vertebra showed multiple bony lesions, noted as Schmorl’s nodes, at the inferior endplates of the T6-T11, and superior endplate of the T11 vertebra, in accordance to the location of severe pain during palpation. Conclusion: SN is associated with disc degeneration due to osteonecrosis process which leads to ischemia in the vertebral body. Microtrauma from excessive physical exercise could also contribute to the herniation through the weak points of the vertebral endplates. Knowledge and awareness of SN as one of the causes for acute or chronic back pain is essential for deciding early examination and diagnosis. Therefore, appropriate management could be delivered.